Worldwide Usage of International Classification of Primary Care - Basílio, Nuno (2016)
To describe the worldwide use of the International Classification of Primary Care (ICPC) and other classifications in primary care settings and to identify details of ICPC use in each country. Methods: A research survey with a questionnaire requiring self-completion was emailed to members of the WONCA International Classification Committee (WICC) and family physicians (FP) from each country recognized by the United Nations (UN). Results: We obtained the e-mail addresses of representatives from 109 countries and received 61 responses (out of 259 requests sent) to the questionnaire from 52 different countries; 30 were obtained from Europe, 8 from Asia, 7 from America, 6 from Africa, and 1 from Oceania. In 34 countries (17%), a version of ICPC was available in a national language. ICPC was used in primary care setting in 27 countries (14%), but it was a mandatory standard in only 6 (3%). Assessment of the topics accounted for in the clinical records showed that 10 countries used ICPC to classify the patient’s reasons for encounter and diagnosis, while just 5 countries used ICPC to classify the patient’s reasons for encounter, diagnosis, and processes of care. Of the 24 countries responding that the use of ICPC for clinical records was not promoted in primary care, 19 used the 10th edition of the International Classification of Diseases (ICD), 3 used other classifications, and 2 did not use any classification. Conclusions: Although the response rate to the questionnaire was low, we concluded that ICPC use is not widespread globally. Even for those countries reporting the use of ICPC in primary care, it is usually not a mandatory standard.